Pengaruh Fasilitas Belajar dan Lingkungan Keluarga terhadap Motivasi Belajar Siswa SMK Kesehatan 2 Tambrauw - Timisela, Yanti; Longkutoy, Meyta; Rumbewas, Adolfince (Universitas Pahlawan Tuanku Tambusai, 2024)
This ponder points to analyze the Impact of Learning Offices and Family Environment on Understudy Learning Inspiration at SMK Kesehatan 2 Tambrauw, The information examination strategy utilized is quantitative expressive investigation. The comes about of the t-test, the autonomous variable in part, the t-value of Learning Offices features a positive/significant impact on the subordinate variable, where the t-value of the Learning Offices variable is tcount 4.821> from ttable 1.6939, or the noteworthiness esteem is 0.000 littler than 0.05. This implies that since t-count> t-table, it can be concluded that the speculation (H1) is acknowledged, the Family Environment variable is tcount 3.081> from ttable 1.6939, or the noteworthiness esteem is 0.000 littler than 0.05. This implies that since t-count> t-table, it can be concluded that the theory (H2) is acknowledged. The comes about of the F test gotten an Fcount esteem of 17.283 with a centrality of 0.000. appears importance